2020
DOI: 10.4314/ahs.v20i4.53
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of postpartum depression among postnatal women in Lagos, Nigeria

Abstract: Background: Globally, postpartum depression is one of the most common but often unrecognized complications of childbirth, yearly affecting about 10–15% of postnatal women. This study aimed to determine the prevalence of postpartum depression and its predictors among postnatal women in Lagos. Methods: A descriptive cross-sectional study was conducted among 250 mothers in Eti-Osa Local Government Area of Lagos State, Nigeria, attending six Primary Health Care centers for infant immunization at six weeks po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 43 publications
7
14
2
Order By: Relevance
“…26 In the study conducted by Adeyemo et al on the other hand, multiparity was found to have increased postpartum depression risk. 27 Different from the present study, in the study conducted by Roysted-Solas et al, older age of the mother was determined to be related with postpartum depression. 28 Society-based study results…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…26 In the study conducted by Adeyemo et al on the other hand, multiparity was found to have increased postpartum depression risk. 27 Different from the present study, in the study conducted by Roysted-Solas et al, older age of the mother was determined to be related with postpartum depression. 28 Society-based study results…”
Section: Discussioncontrasting
confidence: 88%
“…There are studies in the literature that examined the effect of UI on women's psychological and social status. 1,4,5,[9][10][11][12][13][14][15][16]18,19,[25][26][27][28][29][30][31][32] A limited number of these studies were conducted on women with postpartum UI. 13,14,18,32 In this study, it was determined that postpartum UI was a common problem which affected one-fifth of the women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from other countries in Africa have also shown discrepancies in PPD prevalence. One study carried out in Nigeria among six weeks postpartum mothers reported a prevalence of 35.6% which is in same range as the present study 26 . The highest reported prevalence of 61.8% and 50.4% within 12 months postpartum were reported in Lime, Cameroon and DRC respectively 27 ; 28 .…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of maternal postpartum depression is also high in Nigeria, with prevalences of 22.9% and 35.6% reported amongst mothers attending postpartum clinics in Enugu [10] and Lagos states [11], respectively. In many cultures, mothers are the main custodian of their child's health [12].…”
Section: Introductionmentioning
confidence: 99%